Effects of makeup air on atrium smoke conditions: A review. Issue 1 (January 2023) - Lei, Wenjun; Qi, Yue; Li, Angui; Mei, Sen
Makeup air is important for fire smoke control systems, and the effects of makeup air on atrium smoke conditions have long been a concern. Requirements for makeup air velocities and makeup air inlet arrangements are too broad in most standards. Herein, the relevant requirements for the design parameters of makeup air given in standards are summarized, and a comprehensive review of factors that influence makeup air and the corresponding effect on smoke management during atrium fires is provided. These influencing factors are divided into uncontrollable factors (wind, external temperature, the location of fire development and the power of the fire) and controllable factors (layout of makeup air inlets and mechanical makeup air velocity). Due to advancements in makeup air systems, the behavioural characteristics of occupants can now be taken into account in the design stage of makeup air systems. Regarding air supply in the breathing zone, the fresh air provided by a makeup air system can be directly supplied to occupants to reduce harmful effects of smoke and avoid casualties. However, determining how to effectively design a makeup air distribution system and the applicability of this type of air distribution in various complex fire conditions requires further study.